2018
DOI: 10.1177/0954406217752025
|View full text |Cite
|
Sign up to set email alerts
|

A new modularization method of heavy-duty machine tool for green remanufacturing

Abstract: The green remanufacturing constitutes a type of recycling form that adapts to ecological and economic requirements and an important part of the advanced manufacturing technology. In order to improve the green remanufacturing capacity of heavy-duty machine tools, in this paper a heavy-duty machine tool module division method for green remanufacturing was proposed. The main lines were based on the four design domains of axiomatic design and innovatively extended to the remanufacturing domain. In the design stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Regarding design and development, many studies in the literature, such as Cheng et al [70], have discussed the remanufacturing phases, where a heavy-duty machine tool method was proposed for green remanufacturing. The axiomatic design was used along with an algorithm based on atomic theory utilization in the study.…”
Section: Design and Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding design and development, many studies in the literature, such as Cheng et al [70], have discussed the remanufacturing phases, where a heavy-duty machine tool method was proposed for green remanufacturing. The axiomatic design was used along with an algorithm based on atomic theory utilization in the study.…”
Section: Design and Developmentmentioning
confidence: 99%
“…The study extended the design process into many different domains, including customer domain and process domain. Similarly, a heavy-duty gantry milling machine was used to verify the method used by Cheng et al [70] for green manufacturing of heavy-duty machine tools. Their module contributed to design efficiency support in remanufacturing.…”
Section: Design and Developmentmentioning
confidence: 99%
“…Smith and Yen 13 proposed a method of product modularity for green design using atomic theory considering green constraints, such as material compatibility, recyclability, and disassemblability. Cheng et al 15 proposed a module division method of the heavy‐duty machine tool for green remanufacturing based on axiomatic design, and extended the process of remanufacturing to design domains, but did not consider the characteristics of various stages of the product life cycle. Sakundarini et al 12 identified the relationship between product end of life strategies and modular design from the aspects of functionality, structure, disassembly ability and materials.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The functions of a product are satisfied by physical structures composed of components. The strength between components affected by function is evaluated by how important the two components contribute to the realization of the function 15 …”
Section: Fuzzy Correlation Analysis Among Components For Remanufacturingmentioning
confidence: 99%
See 1 more Smart Citation